Spring Security Core Beginner to Guru - Thompson, John (Packt Publishing, 2020)
Understand how to protect Java framework applications by learning cutting-edge Spring Security techniques About This Video Gain a deep understanding of Spring Security Explore the Spring Security toolset for authentication and authorization of users Become familiar with the Test-Driven Development (TDD) approach In Detail Increasing cases of online security breaches have made it important for every organization to ensure that their applications are secure. With this video course, you'll explore Spring Security techniques that'll help you in authenticating and authorizing users, and protecting your applications from hazardous security breaches. The course begins with an introduction to Spring Security, enabling you to understand its importance in securing framework applications. You'll leverage the auto-configuration capabilities of Spring Boot to secure a web application using HTTP basic authentication. Next, you'll learn how to replace and customize the default Spring Boot auto-configuration with the help of a series of exercises. Moving ahead, you'll discover the unique security aspects in a Spring Boot web application that mimics a robust monolithic application with web pages and RESTful endpoints. Later, you'll follow a Test-Driven Development (TDD) approach to understand the features of Spring Security. With the help of interesting examples, you'll also be able to write a failing test using JUnit 5, Mockito, and Spring MockMVC By the end of this video course, you'll have developed the skills you need to use Spring Security to secure your framework applications.
Online resource; Title from title screen (viewed September 30, 2020)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos